Comportamiento agronómico de la papa (Solanum tuberosum) variedad chaucha cultivada en tres distancias de siembra - Guevara Vizuete, Willams Fernando (2015)
This research aimed to determine the agronomic performance of the potato (Solanum tuberosum L.) cultivated variety chaucha three planting distances. Treatments were T1 (0.8 x 0.35), T2 (0.8 x 0.30), T3 (0.8 x 0.25) and T4 (1.0 m between rows x 0.40 m between sites). He was held in the parish Belisario Quevedo Canton Latacunga, Cotopaxi province, whose geographical location is 00° 93' 00'' south latitude and 78° 61' 00'' west longitude, with an altitude of 2955 meters. The experimental work lasted six months. The specific objectives were proposed for this research were to determine the best production of treatments, identify the best planting distance that produce better results in potato cultivation and economically analyze treatments. The variables evaluated were subjected to analysis of variance and to establish statistical difference between treatments means the Tukey test were used 0.05 and 0.01% probability. The experimental design used was a D.B.C.A. (Design Randomized Complete Blocks) with 4 treatments and 4 replications. From the results obtained in the field is to be the best production 21.77 tons/hectare of potato variety chaucha presents the T2 treatment in which the tubers are grown at a distance of (0.8 m between rows and 0, 30 m between sites ). The greatest benefit/cost ratio 1.97 has the T2 treatment in which the tubers grown at 0.8 m between rows x 0.30 m between sites.